Respuesta :
We know that x^m * x^n = x^( m + n ).
And the seventh root of x to the fifth power is: [tex] \sqrt[7]{ x^{5} } [/tex]
Therefore:
[tex] \sqrt[7]{ x^{5} } * \sqrt[7]{ x^{5} } = \\ = \sqrt[7]{ x^{5} * x^{5} }= \\ = \sqrt[7]{ x^{10} }= \sqrt[7]{ x^{7} }* \sqrt[7]{ x^{3} }=x* \sqrt[7]{ x^{3} } [/tex]
Answer: D ) x times the seventh root of x cubed.
And the seventh root of x to the fifth power is: [tex] \sqrt[7]{ x^{5} } [/tex]
Therefore:
[tex] \sqrt[7]{ x^{5} } * \sqrt[7]{ x^{5} } = \\ = \sqrt[7]{ x^{5} * x^{5} }= \\ = \sqrt[7]{ x^{10} }= \sqrt[7]{ x^{7} }* \sqrt[7]{ x^{3} }=x* \sqrt[7]{ x^{3} } [/tex]
Answer: D ) x times the seventh root of x cubed.
Answer:
x times the seventh root of x cubed.
Step-by-step explanation:
We know that x^m * x^n = x^( m + n ).
And the seventh root of x to the fifth power is: \sqrt[7]{ x^{5} }
Therefore:
\sqrt[7]{ x^{5} } * \sqrt[7]{ x^{5} } = \\ = \sqrt[7]{ x^{5} * x^{5} }= \\ = \sqrt[7]{ x^{10} }= \sqrt[7]{ x^{7} }* \sqrt[7]{ x^{3} }=x* \sqrt[7]{ x^{3} }